Chemogenetic inhibition of corticostriatal circuits reduces cued reinstatement of methamphetamine seeking. (25th August 2021) - Kearns, Angela M.; Siemsen, Benjamin M.; Hopkins, Jordan L.; Weber, Rachel A.; Scofield, Michael D.; Peters, Jamie; Reichel, Carmela M.
Abstract: Methamphetamine (meth) causes enduring changes within the medial prefrontal cortex (mPFC) and the nucleus accumbens (NA). Projections from the mPFC to the NA have a distinct dorsal‐ventral distribution, with the prelimbic (PL) mPFC projecting to the NAcore, and the infralimbic (IL) mPFC projecting to the NAshell. Inhibition of these circuits has opposing effects on cocaine relapse. Inhibition of PL‐NAcore reduces cued reinstatement of cocaine seeking and IL‐NAshell inhibition reinstates cocaine seeking. Meth, however, exhibits a different profile, as pharmacological inhibition of either the PL or IL decrease cued reinstatement of meth‐seeking. The potentially opposing roles of the PL‐NAcore and IL‐NAshell projections remain to be explored in the context of cued meth seeking. Here we used an intersectional viral vector approach that employs a retrograde delivery of Cre from the NA and Cre‐dependent expression of DREADD in the mPFC, in both male and female rats to inhibit or activate these parallel pathways. Inhibition of the PL‐NAcore circuit reduced cued reinstatement of meth seeking under short and long‐access meth self‐administration and after withdrawal with and without extinction. Inhibition of the IL‐NAshell also decreased meth cued reinstatement. Activation of the parallel circuits was without an effect. These studies show that inhibition of the PL‐NAcore or the IL‐NAshell circuits can inhibit reinstated meth seeking. Thus, the neural circuitry mediating cued reinstatement of meth seeking is similar to cocaine in the dorsal, but not ventral, mPFC‐NA circuit. Abstract : The present studies were designed to test the roles of prelimbic (PL)‐NAcore and IL‐NAshell in meth seeking. Importantly, previous studies only manipulated individual brain sites in meth models; here, we addressed the importance of these medial prefrontal cortex (mPFC)‐NA subcircuits at the level of individual neural pathways in meth seeking. We report that inhibition of both the PL‐NAcore and IL‐NAshell decreased meth seeking and activation of both pathways did not alter cued relapse.